Correspondence: reply to 'On the nature of strong piezoelectricity in graphene on SiO2' - Rodrigues, Gonçalo da Cunha (2017)
In our paper we provided an experimental evidence that the single-layer graphene (SLG) deposited on SiO 2 grating substrate exhibits very strong out-of-plane piezoelectric effect, several times greater than that of the best piezoceramics such as lead-zirconate titanate.